Perception Towards Illness/Treatment and Satisfaction Towards Healthcare Services in the Advanced Level Referral Health Facilities - Ryan Astaruddin; Dwi Endarti; Tri Murti Andayani; Tuangrat Phodha (Center for Health Economic Studies, 2023)
Since it was enacted in 2014, it has been reported that the number of JKN participants has increased every year. This increase was influenced by perceptions of illness, perceptions of treatment, and service satisfaction. This study aims to describe perception towards illness/treatment and satisfaction towards satisfaction of health services in the advanced level referral health facility (FKRTL) among national health insurance (JKN) participants and determine the relationship between sociodemographic characteristics and the perceptions and satisfaction. Method: This research is an analytic observational study with a survey data collection using a cross-sectional approach. The study used a convenience sampling technique with a minimum sample size of 400 respondents. The survey was conducted online to cover respondents from all areas of Indonesia. Result: The study showed that 220 respondents (55%) had positive perceptions of illness, 213 respondents (53.2%) had positive perceptions of treatment, meanwhile 217 respondents (54.2%) %) had a satisfied perception of health services. There was a significant relationship between income level and the perception of illness (p=0.048). Conclusion: Most of the respondents have a positive perception of illness and medicine. In addition, some respondents were satisfied with the health services at the advanced-level referral health facility. The income level variable has a significant relationship with the perception of pain.